Spatial architecture of neurovascular unit in the eye and its modulation in Mitfmi-enu22(398) mice with retinopathy - Svärd, Samuel (My University, 2024)
A multimodal imaging workflow was established and utilized to studying retinal architecture and neurovascular coupling in retinopathies, specifically characterizing homozygous Mitfmi-Enu22(398) mice with abnormal retinal pigment epithelium (RPE). The impact of mutated microphthalmia-associated transcription factor (MITF) on the RPE, photoreceptors, and other retinal layers was investigated through three-dimensional multiplexed immunofluorescence, in situ enzyme histochemistry and scanning electron microscopy of retinal tissues. Significant changes were observed in Mitfmi-Enu22(398) eyes, including retinal thickening due to the loss and redistribution of melanosomes, reactive macro- and microgliosis, and excessive neovascularization. Additionally, several therapeutically relevant purinergic targets and biomarkers of retinopathy were explored. Specifically, reduced activity of ectonucleoside triphosphate diphosphohydrolase-1 (CD39), together with high expression of microglial ATP-specific P2Y12 receptor, ATP-releasing connexin 43 hemichannels on retinal astrocytes, and photoreceptor ecto-5'-nucleotidase/CD73 suggest a central role for extracellular ATP metabolism and signalling in the pathological retinal remodelling and progression of neuroinflammation. This process appears to increase susceptibility to chronic inflammatory responses in the mutated eyes. Collectively, these findings emphasize the importance of single-nucleotide mutations in the maintenance of retinal integrity and function, and highlight the value of the established imaging techniques for studying retinopathies and other ocular pathologies.
Keywords: Retinopathy, microphthalmia-associated transcription factor, neurovascular coupling, three-dimensional multiplexed immunofluorescence, ectonucleotidases